Recreation resources assessment for forest campground planning at Ayer Hitam Forest Reserve, Puchong - Zahari, Nur Adelia (2016)
Forest campground is one of the facilities provided in Ayer Hitam Forest Reserve, Puchong. Due to the long-term utilisation of the current forest campground, the issue of campground identity is recognised. A study using Resource Assessment approach was conducted at proposed study site is to assess the characteristics of the existent resources for ideal structures development and layout plan at Ayer Hitam Forest Reserve. Data was collected in 3 different zones using resource inventory form (RRIF) for 12 weeks. The finding proven that zone 2 had the highest mean score which represent high value of resources. The remains zones proposed for structures and facilities development. These finding followed by proposed sketches and layout of forest campground. Thus, this study may provide valuable information regarding to the RPH and management planning for Ayer Hitam Forest Reserve, Puchong.